Communication and control : issues and aesthetics associated with writing for graphic and traditional notation and the influences of both notational systems on the compositional process - O'Connor, Neil (Trinity College (Dublin, Ireland). Department of Music, 2011)
This dissertation investigates such processes along and addresses the separate methodologies involved in the composition of music using graphical or traditional notation. The impact of either notational system upon compositional and performance processes is analyzed and assessed. In so doing, pertinent issues, such as how the music is perceived (making use of stream segregation, Gestalt psychology and schematic processing) and interpreted, are addressed. This discussion appositely applies to the two strands of the compositional work submitted (using graphical and traditional notation respectively). A number of scores are presented: Modular Motion, Approximate Motion and Framed Motion employ graphic notation; and traditional notation is employed by Passing / Parting / Release and Block / Static / Mass for large ensemble and electronics. By looking at these areas I can uncover the compositional process and examine how I create, communicate and control musical experience.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin